Improving the technology of protection of winter rape from pests in West Polesie - Sekun, N.; Snijok, E. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
Changes in the contamination of winter rapeseed crops have been induced depending on the main tillage system in Western Polesye. The effectiveness of the Lontrell 300 herbicide against annual weed species and its influence on the qualitative and quantitative structure of weed infestation were studied. The possibility of reliable plant protection against rapeseed flower beetle and seed stowage is brought by spraying with Mospilan at the beginning of flowering. Reliable protection of rape from Alternaria is achieved by using the fungicide Colosal Pro. It has been reported that the crop protection system, which includes tillage and chemical protection, contributes to the improvement of plant productivity indicators and overall increase in yield.